Genome-wide identification of myeloblastosis gene family and its response to cadmium stress in Ipomoea aquatica - Liu, Zheng; Zhang, Yuxin; Altaf, Muhammad Ahsan; Hao, Yuanyuan; Zhou, Guangzhen; Li, Xinyu; Zhu, Jie; Ma, Wuqiang; Wang, Zhiwei; Bao, Wenlong (Frontiers in Plant Science, 2022)
The myeloblastosis (MYB) proteins perform key functions in mediating cadmium (Cd) tolerance of plants. Ipomoea aquatica has strong adaptability to Cd stress, while the systematic studies on the roles of the MYB gene family under Cd stress response in I. aquatica are still unclear. Here, we identified a total of 183 MYB genes in I. aquatica (IaMYB) at the whole-genome level, which were classified into 66 1R-type IaMYB, 112 2R-type IaMYB, four 3R-type IaMYB, and one 4R-type IaMYB. The analysis of phylogenetic tree indicated that most of IaMYB genes may be engaged in diverse biological processes including defense, development and metabolism. Analysis of sequence features showed that IaMYB genes within identical subfamily have similar patterns of motifs and gene structures. Analysis of gene duplication events revealed that the dispersed duplication (DSD) and whole-genome duplication WGD) play vital roles in the expansion of the IaMYB gene family. Expression profiling manifests that approximately 20% of IaMYB genes had significant role in the roots of I. aquatica under Cd stress. Promoter profiling implied that the differentially expressed genes might be induced by environmental factors or inherent hormones and thereby execute their function in Cd response. Taken together, our findings lay a foundation for further deciphering the functions of IaMYB genes with respect to Cd stress.